ANALYSIS OF THE GUT CONTENTS OF MERLUCCIUS MERLUCCIUS (NORTHERN HAKE) IN NORTH SEA - Garkuwa, Nuru A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
The genus Merluccius composed of number of economically viable species and is a medium to large demersal species caught in mixed fisheries. Stomachs content of hake (Merluccius) in Northeast Atlantic was analysed on commercial pair trawler. Quantile Regression (QR) was then applied to estimate the relationship between predator size and maximum prey size. In addition, Generalised Additive Model (GAM) was also used to estimate the strengths of the effects of the predator on the prey. The total number of stomachs dissected from the Northeast Atlantic showed 20.6% of the stomachs contained prey (mainly fish, no crustaceans) while 79.4% was empty. Out of the 49 samples bought from the market, only 11(22.5%) stomachs contained prey, while 38 (77.6%) were empty. GAM result shows that the proportion of empty stomachs increases with size. The maximum size of prey consumed increases with increase in length of predator suggesting that adult M. merluccius are piscivorous. The use of survey vessel is recommended for future scientific trips as commercial vessels would not catch juveniles‘ species.